2021
DOI: 10.1007/s11165-021-10036-4
|View full text |Cite
|
Sign up to set email alerts
|

Teaching for Emergent Disciplinary Drawing in Science? Comparing Teachers’ and Children’s Ways of Representing Science Content in Early Childhood Classrooms

Abstract: This classroom-based study aims to contribute knowledge about children’s opportunities to make use of drawing to make meaning in science. Employing a social semiotic approach to drawing, we examine what ways of representing science content that are (1) made available by the teacher and (2) adopted in children’s drawings. We analysed observation data from 11 science lessons in early childhood classrooms (children aged 3 to 8 years), including the drawings that children made during those lessons (129 drawings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…Det finns dock inte så mycket forskning om hur lärare använder aktiviteter där barn får rita i den naturvetenskapliga undervisningen. I ett forskningsprojekt har forskare från Umeå universitet och Örebro universitet i två delstudier [1,2] undersökt hur och varför lärare låter barn och elever rita.…”
Section: Gunnar Höstunclassified
See 1 more Smart Citation
“…Det finns dock inte så mycket forskning om hur lärare använder aktiviteter där barn får rita i den naturvetenskapliga undervisningen. I ett forskningsprojekt har forskare från Umeå universitet och Örebro universitet i två delstudier [1,2] undersökt hur och varför lärare låter barn och elever rita.…”
Section: Gunnar Höstunclassified
“…I den andra delstudien [2] i projektet tittade forskarna Areljung, Skoog och Sundberg närmre på vilka sätt att representera naturvetenskap som lärarna och barnen och eleverna använde. Förutom barnens bilder fotograferade forskarna även det material som lärarna använde, som till exempel böcker, powerpoints och text och bild på whiteboard.…”
Section: Sex Olika Sätt Att Rita I Naturvetenskaplig Undervisningunclassified
“…Indeed, the few teachers who, in the interviews, related drawing to science teaching and learning, were the ones who made explicit use of drawing for science learning in the classroom. In another paper from the same project (Areljung et al, 2021b), it has been highlighted the importance of the drawings produced by teachers. The researchers have found that when a teacher draws a schematic drawing on the blackboard about a plant growth experiment to be conducted, all the children draw it in the same way.…”
Section: Teachers' Readiness To Use Drawings As a Science Teaching St...mentioning
confidence: 99%
“…For example, many images and physical models representing the DS show it just from an external view, and, although these images can be realistic, they do not allow the learner to see the system as a tube, in the way that self-made drawings or physical models can (Uskola et al, 2022). Although this cluster was a minority, the importance of purposefully doing their own drawings in science teaching should be addressed in the training of future teachers, as the importance they give to the strategy could determine their use in science classes (Areljung et al, 2021b).…”
Section: Psts´ Clusters and Educational Implicationsmentioning
confidence: 99%
See 1 more Smart Citation